2022
DOI: 10.3390/jcm11216244
|View full text |Cite
|
Sign up to set email alerts
|

Complications and Implant Survival of Total Knee Arthroplasty in People with Hemophilia

Abstract: Total knee arthroplasty (TKA) is a commonly used option in advanced stages of knee arthropathy in people with hemophilia (PWH). The objective of this article is to determine what the complication rates and implant survival rates in PWH are in the literature. A literature search was carried out in PubMed (MEDLINE), Cochrane Library, Web of Science, Embase and Google Scholar utilizing the keywords “hemophilia TKA complications” on 20 October 2022. It was found that the rate of complications after TKA in PWH is h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…However, several studies have documented the importance of multidisciplinary care and appropriate prophylaxis in achieving successful surgical outcomes in the management of haemophilic arthropathy in patients with inhibitors. 10,11 Our case report is novel, in that it showcases the successful and complication-free implementation of a transfemoral prosthesis in a patient with severe haemophilia A and inhibitors. Moreover, our successful outcome is consistent with findings from another study that reported low rates of complications in patients with bleeding disorders undergoing major surgeries at a haemophilia treatment center.…”
Section: Discussionmentioning
confidence: 90%
“…However, several studies have documented the importance of multidisciplinary care and appropriate prophylaxis in achieving successful surgical outcomes in the management of haemophilic arthropathy in patients with inhibitors. 10,11 Our case report is novel, in that it showcases the successful and complication-free implementation of a transfemoral prosthesis in a patient with severe haemophilia A and inhibitors. Moreover, our successful outcome is consistent with findings from another study that reported low rates of complications in patients with bleeding disorders undergoing major surgeries at a haemophilia treatment center.…”
Section: Discussionmentioning
confidence: 90%
“…The revision rate was 3.70% (3/81) for all TKAs of three groups due to deep infection and aseptic prosthetic loosening in our study. A previous review reported the total complication rate in TKA of hemophilia patients to range between 7% and 30% 14 . However, the rate has decreased within the last two decades due to enhanced perioperative hematologic treatment 14 .…”
Section: Discussionmentioning
confidence: 99%
“…A previous review reported the total complication rate in TKA of hemophilia patients to range between 7% and 30% 14 . However, the rate has decreased within the last two decades due to enhanced perioperative hematologic treatment 14 . Another study further showed that 34% of their patients suffered from postoperative major bleeding, which significantly led to worse functional outcomes and a high complication rate in TKA of hemophilia patients 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation